Evaluation of the effect of walking speeds on human gait recognition - Kadir, Kushsairy Abdul; Makhdoomi, Nahid A.; Gunawan, Teddy Surya; Habaebi, Mohamed Hadi; Mansor, Hasmah (2014)
Human Gait Recognition is typically alluded to imply the human ID by the style/way individuals stroll in picture sequences. Our point is to execute the customary gait recognition calculation and to demonstrate the variety in recognition when subject is watched parallel to camera under three conditions- walking slow, at typical speed and walking quickly. For this situation, the work devises a novel strategy with the end goal of likeness calculation as opposed to the customary idea, where the overall recognition rate of 65% percent was achieved.